2012
DOI: 10.1371/journal.pone.0031964
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure of Apigenin Induces Hepatotoxicity in Swiss Mice

Abstract: Apigenin, a dietary flavonoid, is reported to have several therapeutic effects in different diseases including cancer. Toxicity of Apigenin is however, least explored, and reports are scanty in literature. This warrants dose-specific evaluation of toxicity in vivo. In the present study, Apigenin was administered intraperitoneally to Swiss mice at doses of 25, 50, 100 and 200 mg/kg. Serum levels of alanine amino transferase (ALT), aspartate amino transferase (AST) and alkaline phosphatase (ALP) were measured al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 34 publications
(39 reference statements)
3
60
0
1
Order By: Relevance
“…This is consistent with the results described in a recent publication in which it was found that hepatotoxicity occurred in Swiss mice only when they were treated with concentrations of apigenin of 100 mg/kg bw and greater [37]. It also has been determined that 150 mg/kg bw was the LD 50 value for apigenin given to mice by IP injection [38].…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with the results described in a recent publication in which it was found that hepatotoxicity occurred in Swiss mice only when they were treated with concentrations of apigenin of 100 mg/kg bw and greater [37]. It also has been determined that 150 mg/kg bw was the LD 50 value for apigenin given to mice by IP injection [38].…”
Section: Resultssupporting
confidence: 92%
“…CUR has been reported to reduce TNF-α secretion via down regulation NFκB and PPAR-γ pathway 27 whereas chitosan can directly bind with LPS to reduce interaction with TLR-4 receptors in accordance with previously published reports 21, 28 . 45 Chi-CUR-NC4b also resulted in reduction of oxidative stress as well as neutrophil migration as indicated by levels of myeloperoxidase in tissues, specifically lung and liver. Tissue injury is a most important hallmark in pathophysiology of sepsis usually worsening to organ failure and death.…”
Section: Discussionmentioning
confidence: 93%
“…The samples were analyzed for changes in size and zeta potential 45 after premilling and then 5, 10, 15, and 20 homogenization cycles respectively. The formulation was optimized by varying type (Tween 80 or PF 68) and concentrations (at 1 and 2% w/v) of stabilizers; Number of homogenization cycles (premilling, 5, 10, 15 and 20 cycles respectively) and outcomes were evaluated in 50 terms of NC size, PDI, and zeta potential.…”
Section: Preparation and Optimization Of Plain And Chitosan Coated 35mentioning
confidence: 99%
See 1 more Smart Citation
“…All the mice were cured at or after 120 th day of infection, when compounds 1 -5 were given; . Apigenin showed cytotoxic activity at 8.30 µg/ml and induced hepatotoxicity at 100 and 200 mg/kg whereas it was non-toxic in 25 and 50 mg/kg [25]. In another study, apigenin decreased viability of human hepatoma HepG2 cells up to 42 % [24].…”
Section: Discussionmentioning
confidence: 99%